Organizational Citizenship Behavior in the Educational Context: A Systematic Review of the Role of Work Motivation, Organizational Commitment, Employee Engagement, and Organizational Culture - Yunita Endra Megiati; Henny Suharyati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Organizational Citizenship Behavior (OCB) plays a crucial role in enhancing the effectiveness of educational institutions, yet its determinants remain fragmented across the literature. This study aims to systematically synthesize the role of work motivation, organizational commitment, employee engagement, and organizational culture in shaping OCB among educators. A Systematic Literature Review approach was employed using the PRISMA protocol to ensure a transparent and rigorous selection process. Relevant literature was obtained from Google Scholar, Scopus, and SINTA databases, focusing on publications within the last decade. A total of seventy-four articles met the inclusion criteria and were analyzed using thematic synthesis. The findings indicate that intrinsic motivation acts as a fundamental internal driver of OCB, while affective commitment strengthens emotional attachment that encourages voluntary extra-role behavior. Employee engagement emerges as the most consistent and dominant predictor, reflecting the role of vigor, dedication, and absorption in translating psychological states into proactive actions. Organizational culture functions as both a direct determinant and a moderating factor that reinforces the influence of individual variables. These results highlight that OCB is shaped by the interaction between psychological and organizational dimensions. The study contributes theoretically by integrating multiple determinants into a unified conceptual framework and offers practical implications for educational institutions in developing strategies to enhance educator performance through strengthening motivation, commitment, engagement, and a supportive organizational culture.